The association of race and ethnicity on obstetric patients' COVID‐19 outcomes: A summary of current literature. (29th March 2023) - Mathew, Dave M.; Ampatey, Nicole A.; Aaronson, Jaime A.; Samuels, Jon D.; McCullough, Danielle; White, Robert S.
Abstract: Amidst the ongoing coronavirus disease 2019 (COVID‐19) pandemic, evidence suggests racial and ethnic disparities in COVID‐19‐related outcomes. Given these disparities, it is important to understand how such patterns may translate to high‐risk cohorts, including obstetric patients. A PubMed search was performed to identify studies assessing pregnancy, neonatal, and other health‐related complications by race or ethnicity in obstetric patients with COVID‐19 infection. Forty articles were included in our analysis based on novelty, relevance, and redundancy. These articles revealed that Black and Hispanic obstetric patients present an increased risk for SARS‐CoV‐2 infection and maternal mortality; racial and ethnic minority patients, particularly those of Black and Asian backgrounds, are at increased risk for hospitalization and ICU admission; racial and ethnic minority groups, in particular Black patients, have an increased risk for mechanical ventilation; Black and Hispanic patients are more likely to experience dyspnea; Hispanic patients showed higher rates of pneumonia; and Black patients present an increased risk of acute respiratory distress syndrome (ARDS). There is conflicting literature on the relationship between race and ethnicity and various pregnancy and neonatal outcomes. Several factors may underly the racial and ethnic disparities observed in the obstetric population, including biological mechanisms and social determinants of health.